FOREIGN POLICY AND MILITARY INVOLVEMENT: Case Study: Sudan and Russia Relationship - Risalanisa Dwi Putri; Yoedhi Swastanto; Jonni Mahroza (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This research paper explores the intricate relationship between Sudan and Russia, focusing on the factors that have led to Russian military involvement in Sudan. The study begins by emphasizing the significance of Sudan in the international arena and examines both domestic and international influences that shape Sudan's foreign policy. This research also discusses the internal environment of Sudan, highlighting how domestic political dynamics and economic challenges have created a context conducive to foreign military involvement. The role of external actors, particularly Russia, is examined in detail. The paper outlines Russia's strategic interests in Sudan, including military cooperation and resource acquisition, and how these interests align with Sudan's foreign policy objectives. The analysis includes a discussion of the broader geopolitical implications of Russia's involvement in the region. The study concludes by synthesizing the findings, reiterating the complex interplay between domestic and international factors that have facilitated Russian military presence in Sudan. It emphasizes the need for a nuanced understanding of these dynamics to comprehend the future trajectory of Sudan's foreign policy and military relations.